The trust crisis in healthcare causes, consequences, and cures - Shore, David A. (New York ; Oxford : Oxford University Press, 2007)
This is a comprehensive survey of the causes and consequences of declining trust in healthcare, and provides suggestions for its restoration. The authors identify the elements of trust in the environment of modern healthcare, and analyse the sources of mistrust in key areas of medicine.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical care -- United States; Physician and patient -- United States; Trust -- United States; Patient satisfaction -- United States